Exploring Britain's Hidden World : A Natural History of Seabed Habitats. - Hiscock, Keith (Wild Nature Press, 2018)
Britain's shallow seas are a mysterious domain. They remain largely unseen and unexplored except by marine scientists and divers, who have been documenting their wondrous discoveries over many years. Now, a wealth of information about what lives on and in the seabed has been brought together in one sumptuously illustrated volume.Keith Hiscock describes the incredible variety of marine life that exists around Great Britain, providing a foundation of knowledge for those interested in the natural history of the shallow seabed. He explains how findings are gathered and organised, as well as showing what is out there and how it works. Fascinating, beautiful and often fragile, the habitats and marine life described are essential to the health and productivity of our oceans. Without an adequate, shared understanding of what and where they are, how can we identify and protect them?Exploring Britain's Hidden World is the culmination of 50 years of research by the author to better understand where different subtidal seabed habitats occur and how their associated marine life has come to exist. That quest draws on a rich vein of knowledge obtained by many naturalists, scientists and divers who, for almost 200 years, have described seabed communities and sought to understand their structure and function.Using a minimum of technical terminology, Keith Hiscock combines his interests in marine biology, diving and photography to inform, inspire, and leave a vivid and lasting impression of the marine habitats and species around Britain. He hopes this book will provide new insights, much pleasure, and perhaps some surprises too.